PENGARUH SENAM PILATES TERHADAP INTENSITAS NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PUSKESMAS DELITUA KABUPATEN DELI SERDANG TAHUN 2023 - Silalahi, Rini Debora; Tane, Reisy (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Low back pain (LBP) is a common musculoskeletal problem that can affect approximately two-thirds of pregnant women, with a frequency of up to 76%, and is a major cause of disability. during the second and third trimesters of pregnancy. The pain can be very severe, leading to difficulty with activities of daily living, higher rates of functional disability, increased sick leave and poor maternal health as well as depression, anxiety and insomnia ( Yiridin, et al, 2023). Therefore, based on this data, researchers are encouraged to conduct a study on the effects of Pilates exercise on back pain in third-trimester pregnant women at Delitua Medical Center. This study aimed to determine the effect of Pilates exercise in reducing back pain in pregnant women in the third trimester. This study uses quantitative research data with a quasi-experimental method and a group pre-post test design, specifically groups of subjects are observed before implementing the intervention. This study, using paired t-test, obtained a significant number or p-value (value = 0..000), much lower than the standard significance level of 0..05 or indicating an effect negative in the third year precious is significant (p < a). ​​​​​​​​Therefore, H0 is rejected and Ha is accepted, which means it can be concluded that Pilates training has an effect Significant effect on back pain in pregnant women during this period third trimester of pregnancy at Deli Tua Community Health Center in 2023.